A homozygous splice site mutation in SLC25A42, encoding the mitochondrial transporter of coenzyme A, causes metabolic crises and epileptic encephalopathy - Iuso, Arcangela; Kotzaeridou, Urania; Hoffmann, Georg F. (JIMD reports, 2019)
SLC25A42 is an inner mitochondrial membrane protein which has been shown to transport coenzyme A through a lipid bilayer in vitro. A homozygous missense variant in this gene has been recently reported in 13 subjects of Arab descent presenting with mitochondriopathy with variable clinical manifestations. By exome sequencing, we identified two additional individuals carrying rare variants in this gene. One subject was found to carry the previously reported missense variant in homozygous state, while the second subject carried a homozygous canonical splice site variant resulting in a splice defect. With the identification of two additional cases, we corroborate the association between rare variants in SLC25A42 and a clinical presentation characterized by myopathy, developmental delay, lactic acidosis, and encephalopathy. Furthermore, we highlight the biochemical consequences of the splice defect by measuring a mild decrease of coenzyme A content in SLC25A42-mutant fibroblasts.